2020
DOI: 10.18510/hssr.2020.8372
|View full text |Cite
|
Sign up to set email alerts
|

Developing Self-Assessment Instrument for Measuring Pre-Service Teachers’ Technological Pedagogical Vocational Knowledge

Abstract: Purpose of the study: This study aims to develop a self-assessment instrument for measuring pre-service teachers' Technological Pedagogical Vocational Knowledge (TPVK). The developed instrument reviewed by experts and analyzed for the reliability and the internal consistency. TPVK, as the expansion of Technological Pedagogical Content Knowledge (TPACK), is the basis of effective teaching vocational knowledge with technology. TPVK’s instrument needed to assess the profile of TPVK among pre-service teachers. Ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…The National Qualification Framework curriculum that applies in Indonesia also has the essence of the need for higher education graduates to have collaborative and problem-solving skills and is expected to apply and utilize science and technology in their fields [9], [10]. However, based on the PISA evaluation, it was found that students' collaborative skills in Indonesia were at the bottom of the list [11], [12].…”
Section: Introductionmentioning
confidence: 99%
“…The National Qualification Framework curriculum that applies in Indonesia also has the essence of the need for higher education graduates to have collaborative and problem-solving skills and is expected to apply and utilize science and technology in their fields [9], [10]. However, based on the PISA evaluation, it was found that students' collaborative skills in Indonesia were at the bottom of the list [11], [12].…”
Section: Introductionmentioning
confidence: 99%